Traffic Flow Characteristics of Heterogeneous Pedestrian Stream Involving Individuals with Disabilities. Issue 1 (January 2015) - Sharifi, Mohammad Sadra; Stuart, Daniel; Christensen, Keith; Chen, Anthony
Walking facilities such as walkways and stairs are important infrastructure that must be designed to accommodate pedestrian behavior to be effective. Heterogeneity in pedestrian composition is one important factor generally overlooked in guidelines and handbooks for walking facility design. Specifically, individuals with different types of disabilities are often overlooked because of the lack of available data. In response, a controlled large-scale research project was conducted at Utah State University to study the performance of various walking environments under heterogeneous pedestrian streams involving individuals with visual and mobility impairments. These environments included a passageway, types of angles (right and oblique), bottlenecks, queuing areas, and stairs. The goals of this study were ( a ) to investigate macroscopic characteristics of heterogeneous pedestrian streams in various walking environments by using traffic flow fundamental diagrams and ( b ) to analyze the walking speeds of different pedestrian groups with consideration of congestion. The performance of facilities was evaluated by using macroscopic parameters estimated from calibrated traffic flow models. Speed analyses showed similarities and differences between the behaviors of pedestrian groups. Exploring traffic flow characteristics of a heterogeneous pedestrian stream in various walking facilities may improve the planning and design of such facilities.